Quality assessment of ciprofloxacin tablets - an antimicrobial drug marketed in Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2022)
Ciprofloxacin is a syntheticfluroquinolone derivative. It is prescribed as a potent antibiotic to treat bacterial infections. An attempt was made to assess the quality of six brands of ciprofloxacin tablets marketed in Bangladesh. Various physicochemical tests, viz., weight variation, hardness, friability, disintegration, dissolution and assay for the content of the active ingredient, were performed in accordance with the methods described in the United States Pharmacopoeia 38 (USP 38). UV-Vis spectrophotometric technique was used for dissolution test while High Performance Liquid Chromatography (HPLC) was used to estimate the potency. All the samples passed the physical tests carried out except one sample (code 004), which failed the friability test.Dissolution profile of each brand was satisfactory. All the brands of examined for the content of the active ingredient complied with the limit stipulated in USP 38 for ciprofloxacin except two brands (003 and 004) which showed slightly higher potency of the drug.Jahangirnagar University J. Biol. Sci. 10(1 & 2): 9-17, 2021 (June & December)